Penurunan Persamaan Gelombang Air Dangkal (Shallow Water Wave) Menggunakan Hukum Kedua Newton - Inayatul Farach Ardianty; Tri Widjajanti Widjajanti; Rium Hilum (FMIPA Universitas Papua, 2023)
These waves occur when the surface of the water is disturbed by wind, gravity, earthquakes, or landslides on the seabed. Shallow water waves can be modelled or expressed in mathematical language, namely the shallow water wave equation which is a partial differential equation. The shallow water wave equation is a partial differential equation that describes the fluid flow problem. A system is considered shallow water if the depth of the fluid is much less than its wavelength. Shallow water waves are a phenomenon of classical mechanics which can be described by three simple laws called Newton’s laws of motion. The stages in the research include identifying problems, making assumptions, and forming shallow water wave equations using Newton’s Second Law and the law of conservation of mass. The form of the two-dimensional shallow water wave equation is u_t+〖uu〗_x=-gh_x (x,t). and h_t=-[u(D+h)]_x.